Book review: Mclean, M., Abbas, A., Ashwin, P. 2019. Quality in Undergraduate Education: How Powerful Knowledge Disrupts Inequality. London: Bloomsbury Publishing - Hlengwa, Amanda (Critical Studies in Teaching and Learning, 2023)
Book review of:Mclean, M., Abbas, A., Ashwin, P. 2019. Quality in Undergraduate Education: How Powerful Knowledge Disrupts Inequality. London: Bloomsbury Publishing.